The Quest for an Appropriate Past in Literature, Art and Architecture - Enenkel, Karl A.E; Ottenheym, Konrad Adriaan (Intersections, 2018)
This volume explores the various strategies of construing appropriate pasts in scholarship, literature, art, architecture and literature, in order to create "national", regional or local identities, in late medieval and early modern Europe. Readership: All those interested in the reception of Antiquity and high medieval history (true and false) in early modern in literature, architecture and art, neolatin scholarship, Renaissance architecture, history of ideas, history of literature, and history of humanist scholarship.